Straight to work or a traineeship: a comparison of two pathways - Dockery, Alfred Michael; Stromback, Carl (The Centre for Labour Market Research, 2005)
This paper presents a simple theoretical model of the Australian Traineeship System and goes on to evaluate the early career outcomes of young persons who take up a traineeship shortly after leaving school. The trainees are compared to other school leavers who do not undertake any further education or training after leaving school. Using eight indicators of outcomes, it is found that doing a traineeship does not lead to marked improvements in outcomes although trainees have a stronger commitment to their chosen career and express greater satisfaction with their jobs than young persons who go straight to work.